Analysis Of Judge's Considerations In Determining Iddah And Mut'ah Maintenance In Verste Divorce Decision: Study Of Decision Number 975/Pdt.G/2025/PA.Cjr - Didin Hidayat; Euis Latipah; Susi Neay (Doctoral Program of Social Science Pasundan University, 2026)
Divorce is a socio-legal phenomenon that continues to rise in Indonesia, including in Cianjur Regency, where many divorce cases are decided through verstek (default judgment). This raises issues regarding wives' rights, particularly livelihood iddah and mut'ah, which must still be provided even if the wife is absent in court. This study aims to analyze judicial considerations in determining livelihood iddah and mut'ah in verstek divorce cases, factors influencing the amount, and the application of justice principles. A qualitative-empirical approach was applied through interviews with a judge of the Cianjur Religious Court who handled case Number 975/Pdt.G/2025/PA.Cjr, supported by document analysis and literature review. The findings reveal that decisions are based on Law Number 1 of 1974 and the Compilation of Islamic Law, considering the husband's economic capacity, the wife's standard of living, and marriage duration. Legal, socio-economic, and utility factors also matter. Justice appears in proportional rulings protecting wives' rights without overburdening husbands.